ELOVL5‐mediated fatty acid elongation promotes cellular proliferation and invasion in renal cell carcinoma. Issue 8 (24th June 2022) - Nitta, Satoshi; Kandori, Shuya; Tanaka, Ken; Sakka, Shotaro; Siga, Masanobu; Nagumo, Yoshiyuki; Negoro, Hiromitsu; Kojima, Takahiro; Mathis, Bryan J.; Shimazui, Toru; Miyamoto, Takafumi; Matsuzaka, Takashi; et al.
Abstract: Renal cell carcinoma (RCC) features altered lipid metabolism and accumulated polyunsaturated fatty acids (PUFAs). Elongation of very long–chain fatty acid (ELOVL) family enzymes catalyze fatty acid elongation, and ELOVL5 is indispensable for PUFAs elongation, but its role in RCC progression remains unclear. Here, we show that higher levels of ELOVL5 correlate with poor RCC clinical prognosis. Liquid chromatography/electrospray ionization‐tandem mass spectrometry analysis showed decreases in ELOVL5 end products (arachidonic acid and eicosapentaenoic acid) under CRISPR/Cas9‐mediated knockout of ELOVL5 while supplementation with these fatty acids partially reversed the cellular proliferation and invasion effects of ELOVL5 knockout. Regarding cellular proliferation and invasion, CRISPR/Cas9‐mediated knockout of ELOVL5 suppressed the formation of lipid droplets and induced apoptosis via endoplasmic reticulum stress while suppressing renal cancer cell proliferation and in vivo tumor growth. Furthermore, CRISPR/Cas9‐mediated knockout of ELOVL5 inhibited AKT Ser473 phosphorylation and suppressed renal cancer cell invasion through chemokine (C‐C motif) ligand‐2 downregulation by AKT‐mTOR‐STAT3 signaling. Collectively, these results suggest that ELOVL5‐mediated fatty acid elongation promotes not only cellular proliferation but also invasion in RCC. Abstract : Elevated ELOVL5 expression is associated with poor renal cancer clinical prognosis. ELOVL5 promotes cellular proliferation by inhibiting apoptosis. ELOVL5 promotes cellular invasion via the AKT‐mTOR‐STAT3‐CCL2 signaling pathway.